Snake venomics and antivenomics of Protobothrops mucrosquamatus and Viridovipera stejnegeri from Taiwan: Keys to understand the variable immune response in horses - Villalta Arrieta, Mauren (2012)
The proteomes of the venoms of the snakes Viridovipera stejnegeri and Protobothrops mucrosquamatus from Taiwan were characterized by N-terminal sequencing, MALDI-TOF mass fingerprinting, and collision-induced dissociation tandem mass spectrometry of in-gel generated tryptic peptides. Proteins belonging to the following toxin classes were identified: metalloproteinase, phospholipase A2 (PLA2), serine proteinase, C-type lectin-like, CRISP, l-amino acid oxidase, disintegrin, and peptides (vasoactive and inhibitors of SVMPs). Nine horses were immunized with a mixture of these venoms. All horses developed a satisfactory immune response against lethality of the venom of V. stejnegeri, whereas only three horses reached the accepted neutralizing potency against the venom of P. mucrosquamatus. Antivenoms were prepared from pools of ‘good responder’ (GR) and ‘poor responder’ (PR) horses and compared by antivenomics and neutralization tests. A similar neutralizing response was observed between the GR and PR antivenoms against the venom of V. stejnegeri, whereas antivenom from PR had a lower neutralizing activity against effects of P. mucrosquamatus venom than antivenom from GR. The low potency of the plasma of some horses against this venom is a consequence of the low immunogenicity of the neurotoxic PLA2 trimucrotoxin. Our results provide clues for innovating the immunization scheme to generate improved antivenoms.